Fish Granzyme A Shows a Greater Role Than Granzyme B in Fish Innate Cell-Mediated Cytotoxicity - Chaves-Pozo, Elena; Valero, Yulema; Lozano, Maria Teresa; Rodríguez-Cerezo, Pablo; Miao, Liang; Campo, Vittorio; Esteban, Maria Angeles; Cuesta, Alberto (Frontiers in Immunology, 2019)
Granzymes (Gzm) are serine proteases, contained into the secretory granules of cytotoxic cells, responsible for the cell-mediated cytotoxicity (CMC) against tumour cells and intracellular pathogens such as virus and bacteria. In fish, they have received little attention to their existence, classification or functional characterization. Therefore, we aimed to identify and evaluate their functional and transcriptomic relevance in the innate CMC activity of two relevant teleost fish species, gilthead seabream and European sea bass. Afterwards, we wanted to focus on their regulation upon nodavirus (NNV) infection, a virus that causes great mortalities to sea bass specimens while seabream is resistant. In this study, we have identified genes encoding GzmA and GzmB in both seabream and sea bass, as well as GzmM in seabream, which showed good phylogenetic relation to their mammalian orthologues. In addition, we found enzymatic activity related to tryptase (GzmA and/or GzmK), aspartase (GzmB), metase (GzmM) or chymase (GzmH) in resting head-kidney leucocytes (HKLs), with the following order of activity: GzmA/K∼GzmM>>GzmH>>>GzmB. In addition, during innate CMC assays consisting on HKLs exposed to either mock- or NNV-infected target cells, though all the granzyme transcripts were increased only the tryptase activity did. Thus, our data suggest a high functional activity of GzmA/K in the innate CMC and a marginal one for GzmB. Moreover, GzmB activity was detected into target cells during the CMC assays. However, the percentage of target cells with GzmB activity after the CMC assays was about ten-fold lower than the death target cells, demonstrating that GzmB is not the main inductor of cell death. Moreover, in in vivo infection with NNV, gzm transcription is differently regulated depending on the fish species, genes and tissues. However, the immunohistochemistry study revealed an increased number of GzmB stained cells and areas in the brain of seabream after NNV infection, which was mainly associated with the lesions detected. Further studies are needed to ascertain the molecular nature, biological function and implication of fish granzymes in the CMC activity, and in the antiviral defence in particular.